143 Economics of cool-season annuals or reduced labor supplementation systems for wintering cowcalf pairs - Kelley, William K (J Anim Sci, 2019)
Cattle producers typically feed hay and supplement for a 90 to 120 day window to maintain cows during the winter in Alabama. A 75-day trial evaluated the use of three systems (n = 3 replications per system): 1) rotationally grazed-winter annuals (GWA) on a 14-day rotation, 2) free-choice whole cottonseed (WCS) and bermudagrass hay, or 3) 50% soybean hulls and 50% corn gluten feed (SH:CGF) fed on alternate days at up to 1% BW daily and free-choice bermudagrass hay. GWA had the greatest Total Cost Per Pair Per Day (TCPD) for the 75 day grazing system at $6.58, followed by WCS at $4.73 and SH:CGF at $4.86. Initial and final cow BCS was not different among treatments (P = 0.1558). Cow ADG was greater (P = 0.0370) on GWA than SH:CGF and WCS (0.9, 0.2, and 0.2 kg, respectively), and calf ADG followed a similar pattern (1.5, 1.2, and 1.1 kg/day for GWA, WCS, and SH:CGF, respectively). WCS and SH:CGF were static across trial when only days of trial are considered, but TCPPD decreased linearly (R=.9723) as days on grazing increase. GWA becomes the low cost feed option (with WCS and SH:CGF inputs remaining constant) if trial days were extended to 119 days. This project demonstrates that GWA produces greater animal performance than other project diets, but requires additional grazing days (>119) to be the least cost feeding option.